2015
DOI: 10.1364/ao.54.005983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the optical fiber type on the performances of fiber-optics current sensor dedicated to plasma current measurement in ITER

Abstract: In this paper, we compare, by means of simulations using the Jones formalism, the performances of several optical fiber types (low birefringence and spun fibers) for the measurement of plasma current in international thermonuclear experimental reactor (ITER). The main results presented in this paper concern the minimum value of the ratio between the beat length and the spun period, which allows meeting the ITER current measurement specifications. Assuming a high-birefringence spun fiber with a beat length of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…These sensors often use a phase modulation technique that was originally developed for fiber-optic gyroscopes to measure the phase shift between the left and right circular light beams in a fiber coil around the measured conductor. The accuracy depends on the fibre quality [33] and also on the optical connectors [34].…”
Section: Magnetooptical Current Sensorsmentioning
confidence: 99%
“…These sensors often use a phase modulation technique that was originally developed for fiber-optic gyroscopes to measure the phase shift between the left and right circular light beams in a fiber coil around the measured conductor. The accuracy depends on the fibre quality [33] and also on the optical connectors [34].…”
Section: Magnetooptical Current Sensorsmentioning
confidence: 99%
“…1), a circular birefringence is induced in the fiber resulting in a rotation of the SOP along the fiber loop. Since the light beam passes twice in the loop (after reflecting from the Faraday mirror) and the Faraday mirror adds a 90°extra rotation, the plasma current is given by [16]:…”
Section: Principles Of Focsmentioning
confidence: 99%
“…Recent works published by the authors [16,17] demonstrated that when the FOCS uses a spun fiber with adequate parameters, the ITER specifications regarding the required plasma current measurement accuracy (see Table 1 [1]) can be fulfilled. A spun fiber is characterized by some intrinsic linear birefringence quantified by its beat length L B [26] and by a rotation of its linear birefringence axis along the fiber length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic for high plasma current measurement like in the future ITER (20 MA). Second, the presence of a lead fiber (fiber section situated between the interrogating device and the loop surrounding the vacuum vessel) deteriorates the FOCS performance [6]. To eliminate these issues, a POTDR (Polarization Optical Domain Reflectometer) can be used since a POTDR trace contains information about the SOP spatial evolution along the fibre.…”
Section: Introductionmentioning
confidence: 99%